Interaction between information systems and work in the brazilian banking sector - Elaine Tavares; Hermano Roberto Thiry-Cherques (RAE: Revista de Administração de Empresas, 2011)
This article presents the results of a research to understand the conditions of interaction between work and three specific information systems (ISs) used in the Brazilian banking sector. We sought to understand how systems are redesigned in work practices, and how work is modified by the insertion of new systems. Data gathering included 46 semi-structured interviews, together with an analysis of system-related documents. We tried to identify what is behind the practices that modify the ISs and work. The data analysis revealed an operating structure: a combination of different practices ensuring that the interaction between agents and systems will take place. We discovered a structure of reciprocal conversion caused by the increased technical skills of the agent and the humanization of the systems. It is through ongoing adjustment between work and ISs that technology is tailored to the context and people become more prepared to handle with technology.